Tafsīr-i Shahristānī al-Musammā bi-Mafātīḥ al-asrār wa-maṣābīḥ al-abrār. Volume 1 - al-Shahristānī, Muḥammad b. ʿAbd al-Karīm (Miras Maktoob, ISBN: 9789004365452., 2019)
Muḥammad b. ʿAbd al-Karīm al-Shahristānī (d. 548/1153) was a prominent historian of religions who was well-versed in Islamic theology and the sciences of the Qurʾān. He is mostly known for his Kitāb al-milal wal-niḥal , a ground-breaking history of religions, his Kitāb muṣāraʿat al-falāsifa , a critical exposition of the philosophy of Avicenna (d. 428/1037)-later refuted by Naṣīr al-Dīn Tūsī (d. 672/1274) in his Maṣāriʿ al-muṣāriʿ -and the Mafātīḥ al-asrār wa-maṣābīḥ al-abrār , his partial Qurʾān commentary contained in the present two volumes. The Mafātīḥ al-asrār was written in the final years of Shahristānī's life and clearly bears the stamp of Ismailism, a branch of Shīʿism to which he had been introduced as a young man by his teacher in Qurʾānic studies in Nishapur, Abu ʼl-Qāsim al-Anṣārī (d. 512/1118). Even if the Mafātīḥ al-asrār is a work that remained unfinished, it is a fine and rare specimen of the richness of Ismaili taʾwīl . 2 vols; volume 1.